Managing land-use effects on Northland dune lakes: lessons from the past. Issue 3 (3rd July 2018) - Stephens, Tom; Augustinus, Paul; Rip, Brett; Gadd, Patricia; Zawadski, Atun
ABSTRACT: The Northland region of New Zealand includes numerous high-value, macrophyte-dominated dune lakes. Recent water policy reforms offer limited guidance on managing for aquatic macrophytes. In addition, dune lake histories are poorly known as regular monitoring dates to 2005 AD. Here, ca. 4000 years of lake functional behaviour is reconstructed from sedimentary archives in two Northland dune lakes (Humuhumu and Rotokawau). Results demonstrated that macrophyte dominance is sensitive to catchment erosion and hydrological drawdown. Degradation of macrophyte communities occurred in the nineteenth and twentieth centuries, earlier at Lake Humuhumu than Lake Rotokawau (post-1880 AD and post-1930 AD, respectively). In both lakes, increased erosional influx reduced macrophyte productivity, before later increases to wider trophic state (post-1970 AD). Lake-level decline is linked to increased nutrient loading at Lake Rotokawau but less so, Lake Humuhumu which is more strongly groundwater-fed. In Northland dune lakes, water-level reduction and erosional influx from land use have driven macrophyte degradation.